Dental Insurance in India (International Journal of Food and Nutritional Sciences, 2022)
Health insurance has become one of the primary modes of payment for healthcare services.Even though general health insurance has advanced significantly, it is still notcomprehensive. Dental insurance is almost non-existent in India. Teeth and gums are asimportant as other vital organs in the human body. In India, more than 85% of the populationhas poor oral health. Despite this, only 12.4% of adults go to the dentist to get their teethchecked out and fixed. The cost of dental treatment is one of the major reasons people avoidvisiting a dentist. In India, very few insurance companies cover dental insurance, and theseare also insufficient. Therefore, dental insurance is the need of the hour. This article focuseson the current scenario of dental insurance in India.